CULTURAL GLOBALIZATION AND THE INDIAN EXPERIENCE: A STUDY OF LITERARY REPRESENTATIONS AND IDENTITY FORMATION - Vats, Nidhi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper investigates the influence of globalization on Indian English literature, highlighting how cultural interactions have redefined its narrative and thematic aspects. It is hypothesized that Indian English Literature does not reflect or project; rather it is involved in, cultural interaction. It is this cross-cultural engagement over space and time that influences the thematic and structural aspects of the writings. The analysis examines the intertextual incorporation of ancient Indian texts and folklore, illustrating how these narratives have transcended boundaries and influenced Western literary traditions. Indian English Literature is examined in the context of globalization, with a focus on the defining characteristics of globalization as represented in Indian English Writing. These characteristics manifest themselves as Intertextuality on a truly global scale by virtue of India’s ancient past traditions with modern theoretical perspectives. Most scholars agree that texts from Mahabharata have found their way into Western literary tradition through their direct influence on Greek epics such as those by Homer and Hesiod. Similarly, many of the themes from Panchatantra’ became part of Cherevin’s ‘Isopet’ and stories from Jataka tales have been adapted in master texts such as Machiavelli’s Il Principe. Furthermore, it explores the importance of English as a common language in India, expanding its reach and enabling Indian writers to share a variety of cultural narratives on a global platform.